Status obesitas dan kadar gula darah pada usia produktif - Tsyaniyah, Amalia Augustina; Aisyah, Iseu Siti; Husnul, Nisatami (Nutrition Scientific Journal, 2024)
High blood sugar levels are one of the biomarkers of metabolic syndrome that can develop into degenerative diseases. Blood sugar levels can be influenced by obesity status. This study aims to analyze the relationship between obesity status and blood sugar levels in productive age in the working area of the Mangkubumi Health Center, Tasikmalaya City. This research method is an observational analytic with a cross-sectional approach. The sampling method was carried out by purposive sampling (selection of research locations) and stratified random sampling (sampling) by as many as 125 people of productive age (15-64 years) in Mangkubumi Village, Karikil Village, and Cipari Village. Data collection on obesity status (anthropometry) was conducted using a digital stepping scale (body weight) and stadiometer (height). Physical activity data collection was conducted using a questionnaire. Data collection on blood sugar levels (Fasting Blood Sugar/GDP) was done using a glucometer. Data analysis used the Chi-Square test. The results of the data analysis showed that there was a significant relationship between obesity status and blood sugar levels (p=0.000). Kadar gula darah yang tinggi merupakan salah satu biomarker (penanda) sindrom metabolik yang dapat berkembang menjadi penyakit degeneratif. Kadar gula darah dapat dipengaruhi oleh status obesitas. Penelitian ini bertujuan untuk menganalisis hubungan status obesitas dengan kadar gula darah pada usia produktif di wilayah kerja Puskesmas Mangkubumi Kota Tasikmalaya tahun 2024. Metode penelitian ini merupakan analitik observasional dengan pendekatan cross sectional. Cara pengambilan sampel dilakukan dengan purposive sampling (pemilihan lokasi penelitian) dan stratified random sampling (pengambilan sampel) sebanyak 125 orang usia produktif (15-64 tahun) di Kelurahan Mangkubumi, Kelurahan Karikil, dan Kelurahan Cipari. Pengumpulan data status obesitas (antropometri) dilakukan menggunakan timbangan injak digital (berat badan) dan stadiometer (tinggi badan), pengumpulan data kadar gula darah (Gula Darah Puasa/GDP) dilakukan menggunakan glukometer. Analisis data menggunakan uji Chi-Square. Hasil analisis data menunjukkan bahwa terdapat hubungan yang signifikan antara status obesitas dan kadar gula darah (p=0,000).